2007
DOI: 10.1586/14760584.6.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Immunization strategies for the prevention of pneumovirus infections

Abstract: Pneumoviruses, which are viruses of the family Paramyxoviridae, subfamily Pneumovirinae, are pathogens that infect the respiratory tract of their host species. The human pneumovirus pathogen, human respiratory syncytial virus (RSV), has counterparts that infect cows (bovine RSV), sheep (ovine RSV), goats (caprine RSV) and rodents (pneumonia virus of mice). Each pneumovirus is host specific and results in a spectrum of disease, ranging from mild upper-respiratory illness to severe bronchiolitis and pneumonia wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Among the prominent features of this infection, a minimal intranasal inoculum (30 – 100 pfu) results in robust virus replication within bronchial epithelial cells that is accompanied by profound granulocyte recruitment. In the absence of pharmacologic intervention, PVM infection progresses to pulmonary edema and respiratory compromise, similar to the more severe forms of RSV infection experienced by human infants [ 10 , 11 ]. In our earlier studies, we identified the chemokine CCL3 (MIP-1α) as a crucial component of this inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Among the prominent features of this infection, a minimal intranasal inoculum (30 – 100 pfu) results in robust virus replication within bronchial epithelial cells that is accompanied by profound granulocyte recruitment. In the absence of pharmacologic intervention, PVM infection progresses to pulmonary edema and respiratory compromise, similar to the more severe forms of RSV infection experienced by human infants [ 10 , 11 ]. In our earlier studies, we identified the chemokine CCL3 (MIP-1α) as a crucial component of this inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, RSV and CMV are very different types of virus. RSV is a single-stranded RNA virus of the family Paramyxoviridae and well known to be seasonal [ 23 ]. It is a major cause of lower respiratory tract infections during infancy and childhood.…”
Section: Discussionmentioning
confidence: 99%
“…HRSV and BRSV infection does not cause life-long immunity, and re-infection is usually subclinical (Van der Poel et al 1994 ). HRSV and BRSV diseases share many features, such as similarity in disease development depends on age (Van der Poel et al 1994 ; Grell et al 2005 ; Antonis et al 2010 ), unique lung histopathology (Bennett et al 2007 ), BRSV co-infection with bacteria, such as Mannheimia and Haemophilus species (BRDC) (Srikumaran et al 2007 ). It was also recorded that the significant similarities in the lung structural features with the overlapping clinical symptoms of respiratory disease (Kirschvink and Reinhold 2008 ).…”
Section: Introductionmentioning
confidence: 99%